Does L1 make a difference? Evidence from the receptive vocabulary size of Spanish and German EFL primary school learners. Issue 2 (2nd April 2016) - Agustin Llach, Maria Pilar
Abstract : The present paper explores and compares the receptive vocabulary sizes of two groups of learners of different native languages. One of the most widely used vocabulary size tests is the Vocabulary Levels Test designed by Nation. Some reservations have been raised in relation to the adequacy of the Vocabulary Levels Test to estimate the vocabulary size of learners with Romance languages. In order to examine this reservation, this paper sets out to describe and compare the vocabulary size estimates of two groups of learners with different mother tongues, Spanish and German. A total of 41 German and 41 Spanish native speakers participated in the study. They averaged between 9 and 10 years of age and attended the 4th grade of primary education. Proficiency level tests revealed that their English level was comparable. Analysis of the results of the Vocabulary Levels Test show that mean and median values are very similar between the two language groups and no significant differences could be found. Results are discussed in light of critical constraints on word knowledge and vocabulary acquisition such as age and word origin.